Abȗ Al-‘Alȃ’ Al-Ma‘Arrȋ: His Contribution To Arabic Poetry (Journal of Namibian Studies : History Politics Culture, 2023)
Abȗ al-‘Alȃ’ al-Ma‘arrî (d. 1057 A.D.), one of the most remarkable blind poets, is celebrated as a brilliant and influential figure in Arabic literature, especially during the Abbasid era. This period marked a pivotal shift in Arab society, transitioning from a nomadic way of life to a more urban and cultured existence. Alongside these societal changes, the landscape of Arabic poetry also experienced a transformation. Traditional Arabian verse, known for its elaborate and intricate meters, began to evolve into shorter, more flexible forms. Al-Ma‘arrî's poetic brilliance lies in his mastery of these diverse styles, which often convey themes of deep scepticism and pessimism. Despite this underlying tone of cynicism, his work transcends the limitations of his time, earning him a lasting place in the canon of Arabic literature. His distinct perspective and literary innovation have not only secured his enduring influence in the Arab world but have also garnered significant recognition from Western scholars, making him a revered figure whose poetry continues to inspire admiration today.